The Role of Reward and Punishment in Strengthening Religious Values in Early Childhood Education - Nurul Halisa; Nurhayati; Sita Awalunisah; Andi Agusniatih (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2025)
The development of children’s religious values plays a fundamental role in shaping their character, particularly in helping children distinguish between good and bad behavior, understanding basic worship practices, and recognizing Islamic symbols from an early age. However, learning activities in early childhood education settings often lack reinforcement strategies that effectively engage children and sustain their motivation during religious learning. This study aims to analyze the role of implementing reward and punishment in strengthening religious values in early childhood education. A qualitative descriptive approach was employed, involving 13 children aged 5–6 years. Data were collected through observation, interviews, and documentation. The results indicate that applying rewards and punishments in learning activities can increase children’s motivation, attention, discipline, and understanding of religious concepts. Three aspects showed improvement: recognition of Hijaiyah letters, performance of prayer movements, and knowledge of the Hijri months. Teachers implemented rewards such as praise, applause, and star stickers, while punishment was applied educationally through verbal reminders and task continuation. These results suggest that appropriately implemented reward and punishment strategies, combined with habituation practices, can effectively support the development of religious values in early childhood education settings.